Keragaan dan Produksi Empat Aksesi Katuk (Sauropus androgynus (L.) Merr) dari Sentra Produksi Sayuran Daun, Kecamatan Cibungbulang, Kabupaten Bogor: Performance and Production of Four Katuk (Sauropus androgynus (L.) Merr) Accession from Leafy Vegetable Center, Cibungbulang District, Bogor Regency - Kartika, Juang Gema; Siti Nabila Nur Safha; Ani Kurniawati (Jurnal Hortikultura Indonesia, 2022)
Sauropus androgynus (L.) Merr known as katuk is one of indigenous vegetables in Indonesia that has many benefits, one of them is used to increase mother’s breast milk. The purpose of this research was to determine the performance and production of four katuk accessions from leafy vegetable center, Cibungbulang District, Bogor Regency, West Java. The research was conducted from July to September 2020 at Leuwikopo Experimental Station, Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University. This research used a completely randomized block design (CRBD) with accession as treatment factor (Accession 1, 2, 3, and 4) with three replications. Result showed that accession 2 and accession 3 gived the best result on the component of growth and plant production. Cluster analysis divided four accessions into three clusters at cophentic distance of 0.4. Cluster I only consisted of accession 1. Cluster 2 consisted of accession 2, and cluster 3 consisted of accession 3 and accession 4. Keywords: cuttings, cluster analysis, dendogram, indigenous vegetable, principal component analysis